(untitled) (Symposium on Natural and Applied Sciences, 2026)
Hormonal regulation plays a central role in the physiological development and function of breast tissue. However, prolonged hormonal imbalance, particularly involving estrogen and progesterone pathways, has been strongly associated with the initiation and progression of breast cancer. Hormone receptor–positive breast cancer represents the most common molecular subtype, highlighting the importance of endocrine mechanisms in tumor biology. Excessive estrogen exposure, altered estrogen metabolism, and dysregulation of estrogen receptor (ER) signaling contribute to increased cellular proliferation, genomic instability, and resistance to apoptosis.